Estudos fisiológicos, nutricionais e moleculares de variedades de cana-de-açúcar (Saccharum spp.) sob estresse por alumínio - Oliveira, Mariane de Souza (2018)
Sugarcane is a crop of global importance and has been expanding to areas with soils containing high levels of exchangeable aluminum (Al), which is a limiting factor for crop development in acidic soils. The study of the sugarcane physiological and nutritional behavior, together with patterns of gene expression in response to Al stress, may provide a basis for effective strategies to increase crop productivity in acid soils. Sugarcane varieties were evaluated for physiological parameters, nutrient and Al content in leaves and roots and gene expression by qPCR, with the genes MDH, SDH, both related to the production of organic acids, and SOD, related to the oxidative stress. Al affected the varieties behavior in relation to the studied parameters. The RB928064 showed the highest decrease in nutritional content when submitted to Al stress, higher leaf metal content and decreased transpiration rate and stomatal conductance. The variety RB867515 was the most resilient in relation to nutrient content, with little variation between treatments. It presented higher Al content in the roots, and like the RB935744, did not suffer variation in stomatal conductance and transpiration. For the studied genes, in RB928034 occurred greater MDH expression in leaves and SOD in leaves and roots. In RB935744, SDH was more expressed in leaves and MDH and SOD in roots, whereas for RB867515 all genes were more expressed in the roots. The occurrence of distinct Al responses among the varieties may provide different management strategies, seeking to allocate the less susceptible varieties in the places with Al toxicity. The results contribute to the development of Al tolerant sugarcane varieties, aiming the expression of all its genetic potential with the lower demand of inputs.